Analisis Ekonomi Politik Terhadap Kebijakan Pemerintahan Jokowi Pada Sektor Kawasan Industri Halal (KIH) dan Perbankan Syariah - Ahmad Dahlan; Muhammad Wildan (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
The government of President Joko Widodo in the 2014-2020 is a government led by the main party of the Indonesian Democratic Party of Struggle (PDIP). It's party is nasionalism but in the policy of developing the Halal Industrial Area and Islamic Banking, many breakthroughs have been developed. Through the method of extracting data from the library datas, the Jokowi government from 2014 to 2020 (the limit of this research was carried out) has carried out many policies related to Halal Industrial Area and Islamic banking. In the political economy analysis of the Jokowi government's policies in the Halal Industrial Area sector and Islamic banking, it can be concluded that there is evidence of political intervention in the market like the Keynesian school. However, from the aspect of business actors or market regulation in the sector of Halal Industrial Area and Islamic banking, the Jokowi's government still gives freedom to the market like the Smithian school.